2014
DOI: 10.1016/j.jpba.2014.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry in clinical chemistry: the case of newborn screening

Abstract: Keywords:Newborn screening LC-MS/MS Tandem mass spectrometry Inborn errors of metabolism Clinical chemistry a b s t r a c t Newborn screening (NBS) program is a complex and organized system consisting of family and personnel education, biochemical tests, confirmatory biochemical and genetic tests, diagnosis, therapy, and patient follow up. The program identifies treatable metabolic disorders possibly when asymptomatic by using dried blood spot (DBS). During the last 20 years tandem mass spectrometry (TMS) has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 53 publications
0
50
0
2
Order By: Relevance
“…DBS samples are routinely collected from all neonates born in the Italian regions of Tuscany and Umbria (about 40000/year) for NBS (12). In order to have the highest possible sensitivity, a 2 nd TT for free methylmalonic and 3-OH-propionic acid has been performed since 2007 if first screen C3 value is ≥ 3.3 µmol/L.…”
Section: Methodsmentioning
confidence: 99%
“…DBS samples are routinely collected from all neonates born in the Italian regions of Tuscany and Umbria (about 40000/year) for NBS (12). In order to have the highest possible sensitivity, a 2 nd TT for free methylmalonic and 3-OH-propionic acid has been performed since 2007 if first screen C3 value is ≥ 3.3 µmol/L.…”
Section: Methodsmentioning
confidence: 99%
“…Multiplex MS/MS assays to screen for lysosomal storage disorders in DBS have been developed [51,52]. It was demonstrated that a single DBS specimen can be used for all the analyses.…”
Section: Metabolomic Strategies and Applications In Iemsmentioning
confidence: 99%
“…Second, most MS-based techniques require stringency in sample preparation, and all MS-based techniques face significant challenges in terms of conversion of raw mass spectral data into interpretable readouts. Third, with a few notable exceptions in microbiology (Seng et al, 2009), drug monitoring (Vogeser and Seger, 2008) and newborn screening for inborn errors of metabolism (la Marca, 2014), MS-based techniques have seen little translation into the clinical realm, despite the fact that they have been available for decades.…”
Section: Techniques For Unbiased Screeningmentioning
confidence: 99%